Redox-Related Epigenetic Mechanisms in Glioblastoma: Nuclear Factor (Erythroid-Derived 2)-Like 2, Cobalamin, and Dopamine Receptor Subtype 4 - Schrier, Matthew Scott; Trivedi, Malav Suchin; Deth, Richard Carlton (Frontiers in Oncology, 2017)
Glioblastoma is an exceptionally difficult cancer to treat. Cancer is universally marked by epigenetic changes, which play key roles in sustaining a malignant phenotype, in addition to disease progression and patient survival. Studies have shown strong links between the cellular redox state and epigenetics. Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) is a redox-sensitive transcription factor that upregulates endogenous antioxidant production, and is aberrantly expressed in many cancers, including glioblastoma. Methylation of DNA and histones provides a mode of epigenetic regulation and cobalamin-dependent reactions link the redox state to methylation. Antagonists of dopamine receptor subtype 4 (D4 receptor) were recently shown to restrict glioblastoma stem cell growth by down-regulating trophic signaling, resulting in inhibition of functional autophagy. In addition to stimulating glioblastoma stem cell growth, D4 receptors have the unique ability to catalyze cobalamin-dependent phospholipid methylation. Therefore, D4 receptors represent an important node in a molecular reflex pathway involving Nrf2 and cobalamin that influences redox and methyl group donor availability. In this article, we describe the redox-related effects of Nrf2, cobalamin metabolism, and the D4 receptor on the regulation of the epigenetic state in glioblastoma.